Evaluación y tratamiento de residuos sólidos domésticos generados por las familias del conjunto habitacional Jaime Baltasar Martínez de Compagnon y Bujanda FONAVI - 2009 - Murga Montoya, José Elías (2011)
In the present study the assessment and treatment of domestic solid waste generated by the families of the Housing Complex and Baltasar Jaime Martinez of Comapagnon and Bujanda - FONAVI, whose objective is to evaluate qualitatively and quantitatively the generation of solid waste, characterizing and determining the per-production capita, using the method of solid waste analysis recommended by the Pan American Sanitary Engineering (CEPIS) and Dr. Carlos Manuel Caycho Chumpitaz, the same that have been used in different districts of metropolitan Lima and the rest of the country determine the number and characteristics of household solid waste from statistical sampling and laboratory analysis to determine the per- capita generation, volumetric weight and the percentage of recoverable and non- recoverable products, in order to take alternate Management Solution and waste disposal. Among the main results is the determination of 0492 per-capita kg / person / day with a density of 222.48 kg/m3. The per-capita generation of solid waste is an important parameter for decision making in regard to design and design management systems and disposal of waste.